2006
DOI: 10.1007/s00425-005-0218-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a cDNA clone (PcSrp) encoding serine-rich-protein from Porteresia coarctata T. and its expression in yeast and finger millet (Eleusine coracana L.) affording salt tolerance

Abstract: A 1.4 Kb cDNA clone encoding a serine-rich protein has been isolated from the cDNA library of salt stressed roots of Porteresia coarctata, and designated as P. coarctata serine-rich-protein (PcSrp) encoding gene. Northern analysis and in situ mRNA hybridization revealed the expression of PcSrp in the salt stressed roots and rhizome of P. coarctata. However, no such expression was seen in the salt stressed leaves and in the unstressed tissues of root, rhizome and leaf, indicating that PcSrp is under the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Moreover, the K + content in the roots and leaves of the transgenics was higher than the WT plants but with no obvious difference in the Na + content between the two. A serine protein gene (PcSrp) from P. coarctata afforded salt tolerance when expressed in finger millet (Mahalakshmi et al 2006). The transgenic millet showed significantly higher root length, shoot length, and seedling fresh weight after 1 mo of salt stress (250 mM NaCl).…”
Section: Genetic Engineering With Halophytic Genes To Improve Salt Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the K + content in the roots and leaves of the transgenics was higher than the WT plants but with no obvious difference in the Na + content between the two. A serine protein gene (PcSrp) from P. coarctata afforded salt tolerance when expressed in finger millet (Mahalakshmi et al 2006). The transgenic millet showed significantly higher root length, shoot length, and seedling fresh weight after 1 mo of salt stress (250 mM NaCl).…”
Section: Genetic Engineering With Halophytic Genes To Improve Salt Tomentioning
confidence: 99%
“…There are a few reports on utilizing the genes from monocot halophytes (A. littoralis, P. coarctata, Aneurolepidium chinense, etc.) for crop improvement (Inada et al 2005; Das-Chatterjee et al 2006;Mahalakshmi et al 2006;Shiro et al 2007;Zhang et al 2008), but progress achieved so far in monocots to understand the molecular basis of salt tolerance is not comparable to that achieved in dicot halophytes. This warrants finding a suitable monocot halophyte model to understand and exploit its salt tolerance mechanism (Flowers and Colmer 2008).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…As the glyceraldehyde-3-phosphate dehydrogenase gene was transferred into yeast cells, and yeast transformants exhibited significantly higher resistance to cold, salt, heat, and drought stresses than controls. In addition, Mahalakshmi et al (2006) reported that expression of the serine-rich protein gene from Porteresia coarctata conferred increasing NaCl tolerance in yeast. Wang et al (2005) cloned the novel Ca 2+ -permeable channel gene, TaTPC1, from wheat and expression of TaTPC1 in a yeast mutant lacking CCH1 recovered its growth under lithium stress.…”
Section: Introductionmentioning
confidence: 99%
“…The functional relevance of stress-responsive genes is being elucidated either by overexpression (Mahalakshmi et al, 2006) or down-regulation studies. In this regard, several down-regulation approaches like transposon or T-DNA insertional mutagenesis are being extensively used.…”
Section: Introductionmentioning
confidence: 99%